2017
DOI: 10.1021/jacs.7b08755
|View full text |Cite
|
Sign up to set email alerts
|

Inner-Sphere Coordination of Divalent Metal Ion with Nucleobase in Catalytic RNA

Abstract: Identification of the function of metal ions and the RNA moieties, particularly nucleobases, that bind metal ions are important questions in RNA catalysis. Here we combine single-atom and abasic substitutions to probe functions of conserved nucleobases in ribonuclease P (RNase P). Structural and biophysical studies of bacterial RNase P propose direct coordination of metal ions by the nucleobases of conserved uridine and guanosine in helix P4 of the RNA subunit (P RNA). To biochemically probe the function of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 77 publications
(171 reference statements)
2
20
0
Order By: Relevance
“…In the current PDB data set, through replication of errors, the recurrence of a given binding site may unfortunately not warrant its reliability and, therefore, it is important to keep redundancy issues in mind. More specifically, present data imply that the assertion that "the coordination of Mg 2+ by nucleobases should be considered as a significant factor in the stabilization of RNA structure" (Zheng et al 2015) must be approached with caution and should not be used to support claims regarding the implication of nucleobase carbonyl groups in catalytic mechanisms (Liu et al 2017).…”
Section: Summary and Concluding Remarksmentioning
confidence: 85%
“…In the current PDB data set, through replication of errors, the recurrence of a given binding site may unfortunately not warrant its reliability and, therefore, it is important to keep redundancy issues in mind. More specifically, present data imply that the assertion that "the coordination of Mg 2+ by nucleobases should be considered as a significant factor in the stabilization of RNA structure" (Zheng et al 2015) must be approached with caution and should not be used to support claims regarding the implication of nucleobase carbonyl groups in catalytic mechanisms (Liu et al 2017).…”
Section: Summary and Concluding Remarksmentioning
confidence: 85%
“…However, pre-tRNA recognition by the much more complex and indispensable protein components of eukaryotic RNase Ps is still poorly understood. Kinetic evidences suggested that a conformational change occurs after the formation of the initial ES complex and before 5′-leader cleavage, transforming the ES complex into an active ES* state (7,9,18,24,25). The ES* complex is stabilized by at least two Mg 2+ ions during the transition from ES to ES*, and the functional groups and metal ions in the active site are believed to be repositioned to coordinate the substrate for catalysis (19,26).…”
mentioning
confidence: 99%
“…The phosphodiester bond cleavage is an S N 2-type transesterification reaction, which uses a two-Mg 2+ -ion mechanism that is also used by the group I and group II introns as well as the spliceosome (27)(28)(29)(30). Despite extensive studies, the positions of the catalytic Mg 2+ ions and the composition of the catalytic center in RNase P are still enigmatic because of the lack of structural information of a pre-tRNA substrate-bound RNase P (24,(31)(32)(33)(34)(35)(36)(37)(38)(39). Consequently, the chemical mechanism of this two-Mg 2+ -ion-mediated reaction still awaits to be revealed.…”
mentioning
confidence: 99%
“…Metal ions have important effects on enzyme activity. 24,25 In this study, Co 2+ , Ca 2+ , Mg 2+ , Ni 2+ , and Zn 2+ were tested for their ability to form nanocomposites with NaDC and to encapsulate PLD in aqueous solution ( Fig. 1).…”
Section: Synthesis and Structural Characterization Of Pld@msncmentioning
confidence: 99%